The concomitance of Gitelman syndrome with nephrocalcinosis in a case followed-up for primary biliary cirrhosis - Kırık, Melya Pelin; Hüzmeli, Can (Ukrainian Journal of Nephrology and Dialysis, 2023)
Gitelman syndrome is a rare autosomal recessive renal tubular disease characterized by hypokalemia, metabolic alkalosis, and hypocalciuria. The syndrome develops as a result of various mutations in the SLC12A3 gene. This manuscript aims to highlight the association of Gitelman Syndrome with nephrocalcinosis in a 48-year-old female patient who presented with pain and cramps in the lower limbs.